Informativeness of quarterly earnings in an asymmetric information environment. - Ong, Sok Peng. (2008)
The main aim is extend findings of Landsman and Maydew in an asymmetric information environment to see if quarterly earnings is of value relevance with the introduction of other information sources like announcements and analyst followings.